THE IMPACT OF ONLINE REVIEWS ON ONLINE PURCHASE INTENTION IN TOKOPEDIA (JAKARTA) - Muhammad Aditya Ramadhan; Ivan Nugroho; Alcado Anggramarizky Wisnu (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
Abstract Purpose – The purpose of this research is to examine the type of online reviews; timelines, quantity, valence and its relationship on online purchase intention in e-commerce (Tokopedia) among millennials in Jakarta. Design/methodology/approach – The quantities approach and simple random sampling methodology were use in this research. Data were gathered through a survey instrument, and the partial least square equation modelling (PLS-SEM) technique was subsequently applied to 98 responses. The model explained variation of the major constructs in relation on online purchase intention of e-commerce (Tokopedia) among millennials in Jakarta. Findings – Reviews timelines is the most influential online reviews element towards Jakarta millennial’s online purchase intention for e-commerce. Originality/value – The research project has provided the researcher and marketers with more clarity into the area of online purchase intention for e-commerce products, which is a volatile and dynamic area with continuous uncertainty. Keywords – Online purchase intention, Reviews timelines, Reviews quantity, Reviews valence. Paper type – Research paper